(untitled) (CIPEEX, 2025)
The objective of this abstract was to summarize the medical importance of river blindness. Onchocerca volvulus is a filarial helminth classified in the subphylum Nemathelmintes. This parasite is transmitted to humans through the bite of black flies, belonging to the genus Simulium, popularly known as borracheiro or pium. Infection with Onchocerca volvulus can lead to severe symptoms, including blindness, which occurs when adult worms lodge in the eyes and cause inflammation and damage to eye tissues. Human river blindness, commonly known as river blindness, is one of the most devastating and neglected tropical parasitoses, causing great morbidity in sub-Saharan Africa. The parasite can survive in the host for up to 14 years, and after one year of infection, it can lead to corneal opacification. Prevalence is particularly high in river and stream regions where black flies breed. The disease not only causes blindness but can also lead to skin problems such as severe itching, rashes, and subcutaneous nodules. The life cycle of Onchocerca volvulus is complex and heteroxenic. Black flies ingest microfilariae, which are present in human blood. Inside the fly, microfilariae develop into infective larvae that, when the fly bites another person, are transmitted to the new host. Inside the human body, adult larvae form subcutaneous nodules (onchocercomas) and release microfilariae into the bloodstream. These microfilariae can then be ingested by other black flies, perpetuating the cycle. The diagnosis of river blindness is made through the identification of microfilariae in the blood or skin, or by the presence of subcutaneous nodules. Molecular tests and eye exams may also be used to confirm infection. Treatment has evolved significantly in recent decades. The main approach is the administration of ivermectin, an antiparasitic that kills the microfilariae and reduces the parasite load. Treatment with ivermectin is effective, but it does not eliminate adult worms, which may require repeated treatments over the years. In some regions, control and eradication programs have been successful in reducing the incidence of the disease through mass administration of ivermectin and improving sanitary conditions. The fight against river blindness also includes measures to control black flies, such as the use of insecticides and the creation of environments less prone to the reproduction of vectors. In addition, education and awareness of affected communities are essential to reduce transmission and improve eye health.